Trichilemmoma of the Scalp: An Unusual Presentation: Triquilemoma do Couro Cabeludo: Uma Apresentação Pouco Comum - Santos, Rui Pedro; Ferreira, Olga; Teixeira, Margarida; Brito, Celeste (Gazeta Médica, 2018)
Trichilemmoma is a benign tumor with origin in the ou-ter root sheath cells of the pilosebaceous follicles. The relationship between the human papilloma virus and this neoplasm remain controversial.